2016
DOI: 10.19044/esj.2016.v12n10p112
|View full text |Cite
|
Sign up to set email alerts
|

Conectivismo: Hacia El Nuevo Paradigma De La Enseñanza Por Competencias

Abstract: The three main learning theories most frequently used in the design and creation of instructional environments are behaviorism, cognitivism and constructivism. In the last years, technology has reorganized the way we live, communicate and learn. The arrival of the web 2.0 has greatly increased students' access to the interconnected information required for their professional formation. Scientific and technological progress has impelled innovation as an assertive paradigm of the well-meant development efforts o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 0 publications
0
6
0
1
Order By: Relevance
“…This first part includes all the information relevant to the models, methodologies, strategies integrated with information and communication technologies, which are the theoretical basis of the integration model to be proposed in the U-Learning model [16]. According to the systematic review, no model was found that generally indicates the guidelines of how to integrate information and communication technologies with education focused on U-Learning [9], just models, methodologies and strategies were found for specific cases but not a general model that integrates ICT and connective learning [17,18] into U-Learning [16].…”
Section: Data Analysis and Resultsmentioning
confidence: 99%
“…This first part includes all the information relevant to the models, methodologies, strategies integrated with information and communication technologies, which are the theoretical basis of the integration model to be proposed in the U-Learning model [16]. According to the systematic review, no model was found that generally indicates the guidelines of how to integrate information and communication technologies with education focused on U-Learning [9], just models, methodologies and strategies were found for specific cases but not a general model that integrates ICT and connective learning [17,18] into U-Learning [16].…”
Section: Data Analysis and Resultsmentioning
confidence: 99%
“…Las tres grandes teorías de aprendizajes o paradigmas ante mencionados son las más usadas en la creación de los ambientes educativos, sin embargo, estas fueron planteadas en unas épocas muy diferentes en donde no existía una alta conectividad, la globalización era vista como una utopía, y los retos sociales, ambientales y económicos eran abordados desde una dimensionalidad local y no a nivel planetaria. Con estas nuevas premisas nace el concepto de conectivismo, el cual integra de manera activa a las Tecnologías de la Información y Comunicación (TIC) dentro todo el proceso de enseñanza y aprendizaje (Tumino & Bournissen, 2016).…”
Section: Postpandemiaunclassified
“…According to the systematic review, no model was found that generally indicates the guidelines of how to integrate information and communication technologies with education focused on integrate the models , just models, methodologies and strategies were found for specific cases but not a general model that integrates ICT and connective learning (Tumino and Adventista, 2016) and the principal author (Siemens et al, 2006) into U-Learning (Villa Martinez et al, 2010).…”
Section: Conclusion and Further Workmentioning
confidence: 99%